The glycoconjugate ontology (GlycoCoO) for standardizing the annotation of glycoconjugate data and its application. (23rd February 2021) - Yamada, Issaku; Campbell, Matthew P; Edwards, Nathan; Castro, Leyla Jael; Lisacek, Frederique; Mariethoz, Julien; Ono, Tamiko; Ranzinger, Rene; Shinmachi, Daisuke; Aoki-Kinoshita, Kiyoko F
Abstract: Recent years have seen great advances in the development of glycoproteomics protocols and methods resulting in a sustainable increase in the reporting proteins, their attached glycans and glycosylation sites. However, only very few of these reports find their way into databases or data repositories. One of the major reasons is the absence of digital standard to represent glycoproteins and the challenging annotations with glycans. Depending on the experimental method, such a standard must be able to represent glycans as complete structures or as compositions, store not just single glycans but also represent glycoforms on a specific glycosylation side, deal with partially missing site information if no site mapping was performed, and store abundances or ratios of glycans within a glycoform of a specific site. To support the above, we have developed the GlycoConjugate Ontology (GlycoCoO) as a standard semantic framework to describe and represent glycoproteomics data. GlycoCoO can be used to represent glycoproteomics data in triplestores and can serve as a basis for data exchange formats. The ontology, database providers and supporting documentation are available online (https://github.com/glycoinfo/GlycoCoO ).